2009
DOI: 10.1088/0960-1317/19/3/035008
|View full text |Cite
|
Sign up to set email alerts
|

Pull-in and snap-through instabilities in transient deformations of microelectromechanical systems

Abstract: We analyze transient finite electroelastodynamic deformations of a perfect electrically conducting undamped clamped–clamped beam, a clamped–clamped parabolic arch and a clamped–clamped bell-shaped arch suspended over a flat rigid semi-infinite perfect conductor. The pull-in instability in a beam and the pull-in and the snap-through instabilities in the two arches due to time-dependent potential difference between the two electrodes have been studied. The potential difference is applied either suddenly or is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 69 publications
(110 reference statements)
6
76
1
Order By: Relevance
“…where, (5) is multiplied by the denominator of the electrostatic force term (1-w o -w) 2 in order to reduce the computational cost [31,33]. Then, substituting equation (8) into the resulting equation, multiplying by the mode shape φ j (x), and then integrating the outcome over the normalized domain…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…where, (5) is multiplied by the denominator of the electrostatic force term (1-w o -w) 2 in order to reduce the computational cost [31,33]. Then, substituting equation (8) into the resulting equation, multiplying by the mode shape φ j (x), and then integrating the outcome over the normalized domain…”
Section: Problem Formulationmentioning
confidence: 99%
“…The bistability nature of arches gives them the advantage of exhibiting large motion stroke when moving between the two stable states, which can be advantageous for resonators and other actuation applications because it yields significantly large signal-to-noise ratio. Consequently, the bistability of arches has been thoroughly studied in order to exploit them in useful applications [1][2][3][4][5][6][7][8][9][10]. For example, micro arches are used as microbridges [7], microvalves [11], microelectro switches or relays [12], logic memories [13], micromuscles [14], and micro-optical switches [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach is taken in [26] on which pre shaped buckled beams are designed [27]. In general the physics of curved arches requires additional analysis in order to predict the nonlinear effects due to the curvature of the structures and the snap-through instability [28,29].…”
Section: Bistable Potentials Obtained By Buckling or Snap-through Insmentioning
confidence: 99%
“…A shallow arch is a beam, which is designed and fabricated to be curved without the need for an axial stress or buckling to form its shape. This kind of structure posses a bi-stable behavior, which has drawn attention for MEMS applications, especially as MEMS switches and actuators [12][13][14][15][16][17][18][19]. Recent works using static and transient models [18,19] have shown that initially curved clamped-clamped beams can undergo several scenarios of escapes via snap-through and pull-in instabilities due to DC electrostatic load.…”
Section: Introductionmentioning
confidence: 99%